Breastfeeding practices in women with type 1 diabetes: A discussion of the psychosocial factors and policies in Sweden and Australia. Issue 1 (March 2015) - Rasmussen, Bodil; Skouteris, Helen; Berg, Marie; Nagle, Cate; Morris, Heather; Nankervis, Alison; Sparud-Lundin, Carina
Abstract Background Women with type 1 diabetes (T1DM) face many challenges during their pregnancy, birth and in the postnatal period, including breastfeeding initiation and continuation while maintaining stable glycaemic control. In both Sweden and Australia the rates of breastfeeding initiation are high. However, overall there is limited information about the breastfeeding practices of women with T1DM and the factors affecting them. Similarities in demographics, birth rates and health systems create bases for discussion. Aim The aim of this paper is to discuss psychosocial factors, policies and practices that impact on the breastfeeding practices of women with T1DM. Findings Swedish research indicates that the overall breastfeeding rate in women with T1DM remains significantly lower than in women without diabetes in the first 2 and 6 months after childbirth with no differences in exclusive breastfeeding. Breastfeeding initiation and continuation among women with T1DM in Sweden has been shown to be influenced by health services delivery, supportive breastfeeding polices and socio-economic factors, particular perceived support from social networks and health professionals. Conclusion There is limited research on the impact of attitudes towards breastfeeding, emotional and social well-being and diabetes-related stress on the decision of women with T1DM to initiate and continue to breastfeed for at least 6 months. A more comprehensive understanding of the breastfeeding practices and psychosocial factors operating during the first 6 months after birth for women with T1DM will be instrumental in the future design of interventions promoting initiation and continuation of breastfeeding in Sweden, Australia and elsewhere.